The significance of calcium-sensing receptor in sustaining photosynthesis and ameliorating stress responses in plants - Bai, Rui; Bai, Chunming; Han, Xiaori; Liu, Yifei; Yong, Jean Wan Hong (Frontiers in Plant Science, 2022)
Calcium ions (Ca2+) regulate plant growth and development during exposure to multiple biotic and abiotic stresses as the second signaling messenger in cells. The extracellular calcium-sensing receptor (CAS) is a specific protein spatially located on the thylakoid membrane. It regulates the intracellular Ca2+ responses by sensing changes in extracellular Ca2+ concentration, thereby affecting a series of downstream signal transduction processes and making plants more resilient to respond to stresses. Here, we summarized the discovery process, structure, and location of CAS in plants and the effects of Ca2+ and CAS on stomatal functionality, photosynthesis, and various environmental adaptations. Under changing environmental conditions and global climate, our study enhances the mechanistic understanding of calcium-sensing receptors in sustaining photosynthesis and mediating abiotic stress responses in plants. A better understanding of the fundamental mechanisms of Ca2+ and CAS in regulating stress responses in plants may provide novel mitigation strategies for improving crop yield in a world facing more extreme climate-changed linked weather events with multiple stresses during cultivation.